Growth mechanism of nanoparticles: Theoretical calculations and experimental results - Mariscal, Marcelo (2012)
We report a combined theoretical and experimental study on the growth mechanism of silver and gold nanoparticles. We introduce for the first time the grand-canonical Monte Carlo method to study the growth/dissolution steps of nanoparticle growth mediated by seeds. In particular we found that small changes on the chemical potential, i.e. the activity of the metal ions, produce significant changes on the size and morphologies of the nanoparticles. We have found very good agreements between simulated structures with those observed experimentally by means of scanning electron microscopy.